Preface (Religious dialogue and cooperation, 2026)
From 23-27 June more than 70 scholars from 20 countries from all over the world gathered in Krushevoat the Third World Conference for Religious Dialogue and Cooperation, where we met to discussthe pressing religious conflicts of this world. Religion is often perceived as a problem. The Conferenceexplored how to make religion a resource for international dialogue and peace. Aware that we cannotsolve all problems, as scholars we believe that creating spaces of dialogue between and within religionsoffers valuable opportunities for promoting peace. Religion today is often misused for political purposesand for supporting wars, while secular ideologies try to exclude religion from the public sphere.
Keywords: Preface; Editor-in-chief